(3OQGSI ebGQfIs - (3ahRj eMeO(B, (3SGejs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ(B,s, 2006)
(3jJfGhd gPG GdcJGH GdCMcGe GdYGeI hGdNGUI ddTQcGJ GdJLGQjI, EPG jYQa GdTQcI ChdG hGdTQhW GdYGeI GYbOgG KGfjG, ceG jHMK aj GdTQhW GdehVhYjI GdNGUI HYbO GdTQcI, hGdJj ChdgG JYOO GdTQcGJ ajeG Cf CSGS hLhO GdTQcI gh GdTQcI gh YbO GdTQcI jJQJH Ydi gPG JYOO GdTNhU Gdechfjf dJdc GdTQcI ceG Gfg jPcQ eSGgeI cd TQjc ef MjK QCS GdeGd hjJWQb CKfGA MOjKg Yf GdTQcI Edi GdTNUjI GdeYfhjI ddTQcI hjfhg Edi GfbVGA GdTQcI ajPcQ GdCSHGH GdYGeI dGfbVGFgG ceG jHMK aj cjajI GdJj JJe HgG JUajI GdTQcI hJbSe QCSeGdgG hGdTNU GdPj jbhe HGdJUajI hdG jcJaj HgPG Hd Efg jPcQ CfhGY GdTQcGJ hJUfjagG Edi eNJdaI JHYG deYGjjQ eYfjI hef GdTQcGJ GdJj jPcQgG TQcI GdJVGef hTQcI GdJhUjI GdHSjWI hTQcI GdeMGUI hGdTQcI PGJ GdeSDhdjI GdeMOhOI hTQcI GdJhUjI HGdCSge hcPdc TQcI GdeSGgeI MjK jYQL HGdMOjK Ydi JYQja gPg GdTQcGJ hNUGFUgG hJCSjgG hGfbVGA gPg GdTQcGJ(B.s
(3HjHdjhZQGajG(B: (3U(B.603 -611s
Keywords: (3GdJLGQIs; (3GdTQcGJ(B- (3GdCQOf s; (3GdTQcGJ(B- (3bhGfjf hJTQjYGJ s